Characterization of Snakehead Fish (Channa striata) Meat Simplicia as Raw Material for Wound Healing Drugs - Arsih, Rini Budi; Taurina, Wintari; Andrie, Mohamad (Jurnal Veteriner; Vol 23 No 3 (2022), 2022)
Characterization is the initial stage of standardization to determine the quality of simplicia. The quality of simplicia is influenced by raw materials, manufacturing process, the storage. Snakehead fish from natural ingredients has been shown to contain nutrients that can accelerate wound healing. This study aims to determine the characterization of snakehead fish (Channa striata) and snakehead fish meat simplicia originating from Sungai Itik Village, Kubu Raya Regency, West Kalimantan as raw material for wound healing drug preparations. Characterization was carried out biologically including habitat and morphology, physically including organoleptic, water content, ash content, and acid insoluble ash content, and chemically including protein and albumin qualitative tests. The results of the characterization of snakehead fish come from the waters around the Itik River with environmental conditions that are still not polluted. The head shape of the snakehead fish is like a snakehead, the body is blackish brown with dark band-shaped rows (striata), the belly is white to yellowish-white, and there is a labyrinth. The results of simplicia characterization of snakehead fish meat had a water content of 81.6% and 8.97%, ash content of 0.813% and 5.17%, and acid insoluble ash content of 0.02%. The results of the qualitative test of protein and albumin were declared positive for containing protein and albumin. Based on the results of the characterization that has been carried out, it can be obtained snakehead fish meat simplicia with good quality.